Control difuso para un convertidor CD-CD bidireccional de medio puente (2016)
This article presents the design, simulation, and implementation of a control applied to a half bridge bidirectional direct current to direct current converter. The control strategy is based on fuzzy logic. The control modifies the values of the interrupter’s work cycle controlled by pulse-width modulation in order to assure a specific value of voltage leaving the converter. The control was experimentally validated in a power converter operating both for function in step-down mode and for function in step-up mode. The simulation was carried out in Matlab/Simulink. A test bench was built based on a 2 kW DC-DC converter and the control algorithm was implemented with Labview and compactRIO.